The Role of Sub Studio's Alternative Space on Public Appreciation of Art - Dimas Marjuki; Yelga Praditya Yosidinata; Aulia Hasanah; Reno Ahmad Firmandini (Journal of Interdisciplinary Social Sciences and Humanities, 2025)
This study examines Sub Studio, an alternative art space founded by ISI Surakarta students, and its role in enhancing public art appreciation. Functioning as a multifunctional venue for exhibitions, discussions, and programs like PHK and Bahari, it was analyzed using a qualitative, ethnographic method through interviews and observation. Findings indicate Sub Studio acts as an artistic arena, fostering interaction between artists and the public. It provides an inclusive learning space that builds visitors' understanding and social capital, while offering artists a platform for experimentation and building symbolic capital. However, its broader impact is constrained by limitations in facilities, promotion, and human resources. The study concludes that such alternative spaces hold significant potential to deepen art appreciation through direct engagement and education. Future research should explore strategies for expanding their influence to audiences with minimal prior exposure to art.